2017
DOI: 10.1002/lary.26914
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vocal fold augmentation on cough symptoms in the presence of glottic insufficiency

Abstract: 4. Laryngoscope, 128:1316-1319, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Thirty‐seven articles 2,7,11–13,19,21–23,25,29–33,35–44,46–51,54,55,57,58,60,63 had sufficient information to perform meta‐analysis (Figure 1). There were 30 RCTs 7,19,20,22,23,25–28,30,32,34–37,39,40,42–45,48,50,51,53,56,57,59,62,64 (including three unpublished completed clinical trials 20,27,34 ), 10 retrospective case series, 2,11–13,31,46,49,55,58,63 nine prospective case series, 21,29,33,38,47,52,54,60,61 one prospective cohort study, 24 and one retrospective cohort study 41 . For studies that produced more than one manuscript, each article was assessed for unique patient data 28,40,53,64 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐seven articles 2,7,11–13,19,21–23,25,29–33,35–44,46–51,54,55,57,58,60,63 had sufficient information to perform meta‐analysis (Figure 1). There were 30 RCTs 7,19,20,22,23,25–28,30,32,34–37,39,40,42–45,48,50,51,53,56,57,59,62,64 (including three unpublished completed clinical trials 20,27,34 ), 10 retrospective case series, 2,11–13,31,46,49,55,58,63 nine prospective case series, 21,29,33,38,47,52,54,60,61 one prospective cohort study, 24 and one retrospective cohort study 41 . For studies that produced more than one manuscript, each article was assessed for unique patient data 28,40,53,64 …”
Section: Resultsmentioning
confidence: 99%
“…SLN block – either via injection of local anesthetic with corticosteroid or surgical transection – could provide a potential therapeutic option for NC that avoids the side effects of commonly used medications. Other recently described procedural treatments for NC include botulinum toxin (BTX) injection of laryngeal muscles 12 and vocal fold augmentation with temporary filler, such as methylcellulose or hyaluronic acid 13 …”
Section: Introductionmentioning
confidence: 99%
“…Other procedural treatments for neurogenic cough have been described, including Botox to the laryngeal musculature and injection augmentation . In those with glottic insufficiency, injection augmentation is felt to reduce laryngeal trauma and by feedback, reduce cough symptoms …”
Section: Discussionmentioning
confidence: 99%
“…For those who undergo treatment, several studies have demonstrated improvement of both dysphagia and dysphonia with early initiation of speech therapy, as well as injection laryngoplasty 13,26‐31 . Injection laryngoplasty significantly reduces the rate of aspiration, returning patients to a regular diet 32‐39 . Patients with unilateral VFP who undergo early injection laryngoplasty are less likely to require long‐term medialization procedures in the form of thyroplasty than those who did not receive early injection laryngoplasty 40 .…”
Section: Resultsmentioning
confidence: 99%
“…13,[26][27][28][29][30][31] Injection laryngoplasty significantly reduces the rate of aspiration, returning patients to a regular diet. [32][33][34][35][36][37][38][39] Patients with unilateral VFP who undergo early injection laryngoplasty are less likely to require long-term medialization procedures in the form of thyroplasty than those who did not receive early injection laryngoplasty. 40 Investigations of treatments, like nimodipine in the acute period of VFP, are promising but requires further evaluation before being widely adopted.…”
Section: Statement 1: Immediate Vocal Fold Paralysismentioning
confidence: 99%